Homotopy Perturbation Method and Seventh-Order Boundary Value Problems - Mabood, Fazle; Idrees, Muhammad (International Journal of Applied Mathematical Research, 2012)
Homotopy Perturbation Method (HPM) is employed to find the approximate solution of seventh-order linear and nonlinear boundary value problems. The effectiveness of HPM is illustrated through two examples. The approximate solution of the equations is obtained in terms of convergent series. Interestingly a high accurate result was obtained with only one p-term of the series using HPM. This thus confirms the strength of HPM. Low absolute error indicates that HPM is a promising tool for solving higher order linear and nonlinear boundary value problems.